Disseminated Cryptococcosis in a Non-HIV Patient in Singapore - Jonathan See; Kok Choon Raymond Fong; Humaira Shafi (Case Reports in Infectious Diseases)
We present a case of disseminated cryptococcosis (DC) in a 71-year-old gentleman with systemic lupus erythematosus (SLE) on long-term corticosteroids. He initially presented with right arm cellulitis in a tertiary hospital in Singapore and was subsequently diagnosed with DC involving skin, meninges, blood, and possibly pulmonary involvement. He eventually succumbed to the disease despite prolonged antifungal therapy. Through this case, we wish to highlight an atypical clinical presentation of an uncommon infection and hope to share the importance of considering DC in the differential diagnosis of nonresolving cellulitis among immunocompromised individuals. Mortality and morbidity rates for this condition remain high despite appropriate treatment. Early diagnosis and treatment are crucial for improved outcomes. More research is needed to improve the therapeutic modalities for treatment of DC and to improve the clinical outcomes for this life-threatening condition.